Joseph Conrad's Nostromo - Bloom, Harold (New York : Chelsea House, 1987)
A collection of eight critical essays on Conrad's novel, arranged in chronological order of publication.
Spine title: Nostromo.
Includes index.
Bibliography: p. 131-133.
Keywords: Conrad, Joseph, -- 1857-1924.; Conrad, Joseph, -- 1857-1924.; Sea stories, English -- History and criticism; Revolutions in literature; Sailors in literature; English literature -- History and criticism